Improvement of Landfill Leachate Biodegradability with Ultrasonic Process - Mahvi Amirhossein; Roodbari Aliakbar; Nabizadeh Nodehi Ramin; Naseri Simin; Dehghani Mohammadhadii; Alimohammadi Mahmood (E-Journal of Chemistry)
Leachate from mature landfills is typically characterized by high ammonium (NH4+) content, low biodegradability (low BOD5/COD ratio) and high fraction of refractory and large organic molecules such as humic and fulvic acids. Mature leachate effluents are known to contain recalcitrant and/or non-biodegradable organic substances and biological processes are not efficient in these cases. A promising alternative to complete oxidation of biorecalcitrant leachate is the use of ultrasonic process as pre-treatment to convert initially biorecalcitrant compounds to more readily biodegradable intermediates, followed by biological oxidation of these intermediates to biomass and water. The objectives of this study are to investigate the effect of son catalysts process on biodegradability improvement. Results showed that when applied as relatively brief pre-treatment systems, the sonocatalysis processes induce several modifications of the matrix, which results in significant enhancement of its biodegradability. For this reason, the integrated chemical–biological systems proposed here represent a suitable solution for the treatment of landfill leachate samples with an efficient remediation of the relevant parameters (COD, TOC).